2021
DOI: 10.1093/ndt/gfab313
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immediate humoral response of COVID-19 vaccines in chronic kidney disease patients: the SENCOVAC study

Abstract: Background Chronic kidney disease (CKD) patients are at high-risk for severe Covid-19. The multicentric, observational and prospective SENCOVAC study aims to describe the humoral response and safety of SARS-CoV-2 vaccines in CKD patients. Safety and immediate humoral response results are reported here. Methods Four cohorts of patients were included: kidney transplant (KT) recipients, haemodialysis (HD), peritoneal dialysis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 23 publications
2
41
0
1
Order By: Relevance
“…It is tempting to speculate that markers of immunosenescence may be better predictors of the immune response than chronological age per se. Antibody titers were numerically higher in peritoneal dialysis than in hemodialysis patients in some [72][73][74] , but not all studies 75,76 .…”
Section: Humoral Responsementioning
confidence: 95%
“…It is tempting to speculate that markers of immunosenescence may be better predictors of the immune response than chronological age per se. Antibody titers were numerically higher in peritoneal dialysis than in hemodialysis patients in some [72][73][74] , but not all studies 75,76 .…”
Section: Humoral Responsementioning
confidence: 95%
“… 3 , 4 So far, messenger RNA (mRNA)‐based COVID‐19 vaccines have proven to be the most protective vaccine type against COVID‐19 disease in the normal population and in different chronic kidney diseases (CKDs). 3 , 5 , 6 , 7 CKD and kidney transplantation are important independent risk factors for severe COVID‐19 disease. 8 , 9 , 10 In addition, COVID‐19 disease‐related mortality rates are higher in patients receiving renal replacement therapy (RRT) than in the normal population.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of COVID‐19 vaccines in immunocompromised kidney transplant patients was found to be significantly lower than in other populations. 5 , 6 At the beginning of the COVID‐19 pandemic, it was not understood how effective the vaccines were in these patient groups, as the phase III studies against COVID‐19 did not include CKD, dialysis, or kidney recipients and focused only on normal individuals. However, in studies conducted after the administration of vaccines over time, it has been found that antibody responses are weaker in uremic and immunosuppressive patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport to and from haemodialysis (HD) was a key risk factor for COVID-19 in HD patients early in the pandemic [ 5 ]. Additionally, patients with CKD, and especially kidney transplant recipients, display an accelerated loss of anti-severe acute respiratory syndrome coronavirus 2 antibodies following infection as well as suboptimal response to vaccines [ 6 , 7 ]. Thus the COVID-19 pandemic is expected to have a major impact on KRT incidence and prevalence as well as on incident and prevalent KRT age in the ERA Registry Annual Report from 2020 onwards.…”
mentioning
confidence: 99%